Long-term outcome of patients with inflammatory cardiomyopathies implanted with cardiac defibrillators: a single centre experience. (24th May 2021) - Domenichini, G; Herrera-Siklody, C; Le Bloa, M; Teres Castillo, C; Carroz, P; Graf, D; Pascale, P; Pruvot, E; Porretta, AP
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Arrhythmia management remains a challenge in patients with inflammatory cardiomyopathies and little is known about the clinical characteristics affecting the arrhythmia burden on the long term. Purpose: To identify clinical predictors of ICD therapies among patients with inflammatory cardiomyopathies. Methods: We included all ICD patients implanted in our centre over the last 10 years in a context of inflammatory cardiomyopathy. For each patient, data from implant, device checks and clinical follow-ups were retrospectively collected. Results: A total of 16 patients were identified (11 males, age at implant 50 ± 13 years). Based on the revised 2019 Japanese Circulation Society criteria, a diagnosis of cardiac sarcoidosis was established in all cases. Secondary prevention of sudden cardiac death was the indication for ICD implant in 50% of the patients. In 5 cases a CRT-D device was implanted because of concomitant left ventricular systolic dysfunction and a high grade AV block. During a median follow-up of 5.0 (0.9-6.6) years, 9 patients (56%) received ≥ 1 appropriate ICD treatment for ventricular tachycardia (VT) episodes (ATP only in 3 cases, ATP and shocks in 6 cases) with a median time lag from implant of 65.5 (57.0-314.8) days. Of these 9 patients, 6 were initially implanted for secondary prevention of sudden cardiac death. At the time of ICD therapies, 8 patients were under immunosuppressive treatment and 3 under antiarrhythmic drugs. A cardiac 18F-FDG PET scan was performed in 7 patients and an abnormal FDG uptake, compatible with an active inflammatory status, was documented in all cases. After optimisation of antiarrhythmic drugs, a VT ablation procedure was performed in 3 patients during the first 6 months following the ICD treatment because of recurrent VT. In another 3 patients, a VT ablation was performed 2-5 years after the first ICD treatment and was associated to stereotactic radiotherapy to achieve VT control. Conclusion: In our series, patients affected by inflammatory cardiomyopathy and implanted with an ICD for secondary prevention of sudden cardiac death appear to be at high risk of ICD treatment especially during the first months after implantation. This could be the consequence of a more aggressive underlying inflammatory substrate, especially during the first phases of the disease, whereas the occurrence of VT episodes at later stage appear to be more scar-related. However, further studies on larger populations are required to confirm these observations.